Use of specifications-based grading in an online, asynchronous graduate organic chemistry course - Moster, Caleb A.; Zingales, Sarah Kathryn (Frontiers in Education, 2024)
Specifications-based grading is an alternative grading scheme that emphasizes student proficiency of learning objectives. Course grades are determined by the number of objectives completed rather than the number of points accumulated. At the University of Saint Joseph, CHEM 510 Intermediate Organic Chemistry is the foundation course that all incoming graduate students take in their first semester of the fully online, asynchronous MS programs in Chemistry and Biochemistry. Students in CHEM 510 complete the entire course online and at their own pace within the structured due dates, which presents unique challenges compared with synchronous learning modalities. With these considerations in mind, CHEM 510 was revised to use a specifications-based grading scheme with an a la carte assessment menu and token system. Generally, students found the alternative grading scheme helpful, but they needed additional instructions and time to adjust to the new grading system. By the end of the semester, students expressed their appreciation for the ability to choose their assessment method, work at their own pace, and use the token system for extensions/retakes. The instructor found that implementation of specifications grading took greater time for the initial course setup, but did not require more time than points-based grading once the course began. One large positive outcome was that student-instructor interactions were more frequently about the content of the course rather than grades. Overall, there was a slight increase in the course's pass rate compared to the pass rate prior to the change in grading modality. We believe that the implementation of the a la carte assessment menu accommodates a more diverse population of learners without sacrificing the integrity of student learning. Additionally, we believe that the diverse assessment opportunities were critical for the successful implementation of specifications-based learning in the online classroom environment, though further extension of the menu in synchronous, in-person classroom settings may be challenging.